A survey of knowledge, attitudes, and practices towards skin and soft tissue infections in rural Alaska. Issue 1 (1st January 2016) - Raczniak, Gregory A.; Gaines, Joanna; Bulkow, Lisa R.; Kinzer, Michael H.; Hennessy, Thomas W.; Klejka, Joseph A.; Bruce, Michael G.
Abstract : Background: Community-acquired methicillin-resistant Staphylococcus aureus and methicillin-sensitive S. aureus infections are common to south-western Alaska and have been associated with traditional steambaths. More than a decade ago, recommendations were made to affected communities that included preventive skin care, cleaning methods for steambath surfaces, and the use of protective barriers while in steambaths to reduce the risk of S. aureus infection. Objective: A review of community medical data suggested that the number of skin infection clinical encounters has increased steadily over the last 3 years and we designed a public health investigation to seek root causes. Study design: Using a mixed methods approach with in-person surveys, a convenience sample (n=492) from 3 rural communities assessed the range of knowledge, attitudes and practices concerning skin infections, skin infection education messaging, prevention activities and home self-care of skin infections. Results: We described barriers to implementing previous recommendations and evaluated the acceptability of potential interventions. Prior public health messages appear to have been effective in reaching community members and appear to have been understood and accepted. We found no major misconceptions regarding what a boil was or how someone got one. Overall, respondents seemed concerned about boils as a health problem and reported that they were motivated to prevent boils. We identified current practices used to avoid skin infections, such as the disinfection of steambaths. We also identified barriers to engaging in protective behaviours, such as lack of access to laundry facilities. Conclusions: These findings can be used to help guide public health strategic planning and identify appropriate evidence-based interventions tailored to the specific needs of the region.